KEANEKARAGAMAN ECHINODERMATA (ECHINOIDEA DAN HOLOTHUROIDEA) DI PULAU BAKALAN, BANGGAI KEPULAUAN, SULAWESI TENGAH, INDONESIA - Moh Reza Sese; Annawaty Annawaty; Eddy Yusron (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
The coastal zone of Indonesia, especially in the eastern archipelago, is composed of typical tropical small island ecosystems such as estuaries, coral reefs, seagrass meadows, algal beds, and sandy beaches which are habitats of many groups of marine organisms including Echinoderms. The biodiversity of many small islands in this area was understudied, including Bakalan Island of Banggai Islands in Central Sulawesi. The purpose of this study was to determine the diversity of Echinoderms (Echinoidea and Holothuroidea) in Bakalan Island. This study applied the purposive sampling technique with the 2 x 2 m quadrats were placed along a 100-meter transect with ten-meter intervals. There are nine species of echinoderms found in this study including Salmacis sphaeroides, Mespilia globulus, Tripneustes gratilla, Echinometra mathaei, Diadema setosum, D. savigny, Echinothrix calamaris, Holothuria atra, and Synapta maculata. The first seven species belonging to the class Echinoidea while the latter two belong to the class Holothuroidea.